Thiazide diuretics: 50 years of history or looking into the future - I. V. Fomin (Кардиоваскулярная терапия и профилактика)
The history of thiazide diuretics’ use during the last 50 years is reviewed. The effects of thiazide diuretics on arterial hypertension treatment effectiveness, cardiovascular mortality and cardiovascular morbidity are discussed. In addition, their hemodynamic effects and safety profile are assessed.